2010
DOI: 10.4061/2010/502318
|View full text |Cite
|
Sign up to set email alerts
|

Mechanical Strength and Viscoelastic Response of the Periodontal Ligament in Relation to Structure

Abstract: The mechanical strength of the periodontal ligament (PDL) was first measured as force required to extract a tooth from its socket using human specimens. Thereafter, tooth-PDL-bone preparations have extensively been used for measurement of the mechanical response of the PDL. In vitro treatments of such specimens with specific enzymes allowed one to investigate into the roles of the structural components in the mechanical support of the PDL. The viscoelastic responses of the PDL may be examined by analysis of th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
15
0
1

Year Published

2011
2011
2023
2023

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 39 publications
(17 citation statements)
references
References 63 publications
1
15
0
1
Order By: Relevance
“…In studies by Komatsu et al [16], the relaxation curves of rabbit periodontal ligament was fitted with time constants between 0.2-0.4 s, 2-4 s, and 100-400 s. Wagenseil et al [17] reported that the stress relaxation behavior of fibroblast populated collagen s consists of three time constants between 1-10 s, 10-100 s, and >1000 s. The three exponential term decay model has also been used to describe the Table 1. Table 1 Summary of material parameters in the viscous model (Eq.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In studies by Komatsu et al [16], the relaxation curves of rabbit periodontal ligament was fitted with time constants between 0.2-0.4 s, 2-4 s, and 100-400 s. Wagenseil et al [17] reported that the stress relaxation behavior of fibroblast populated collagen s consists of three time constants between 1-10 s, 10-100 s, and >1000 s. The three exponential term decay model has also been used to describe the Table 1. Table 1 Summary of material parameters in the viscous model (Eq.…”
Section: Discussionmentioning
confidence: 99%
“…Studying the tissue level constitutive behavior, previous studies have shown that the stress-relaxation behavior of collagen based material was well described by a function with three exponential decay terms which reflecting the short-, medium-, and long-term relaxation components in the tissue [16,17]. In studies by Komatsu et al [16], the relaxation curves of rabbit periodontal ligament was fitted with time constants between 0.2-0.4 s, 2-4 s, and 100-400 s. Wagenseil et al [17] reported that the stress relaxation behavior of fibroblast populated collagen s consists of three time constants between 1-10 s, 10-100 s, and >1000 s. The three exponential term decay model has also been used to describe the Table 1.…”
Section: Discussionmentioning
confidence: 99%
“…By contrast, non-mineralized soft biological materials refer to biopolymers such as collagen and viscid spider silk, which possess simultaneously low elastic moduli, large levels of stretchability, and relatively high tensile strengths. Recent studies show that an unconventional J-shaped stress-strain curve, induced by molecular uncoiling and unkinking under low stress, can yield superior mechanical properties (Fratzl et al, 1998; Gautieri et al, 2011; Keten et al, 2010; Komatsu, 2010; Meyers et al, 2013; Miserez et al, 2009; Provenzano et al, 2002; Simmons et al, 1996). Despite promising applications in tissue engineering and biomedical devices, the development of soft synthetic materials with matching mechanical properties has received far less attention (Hong, 2011; Jang et al, 2015; Naik et al, 2014) compared to that of mineralized biological materials, in part due to the complex, irregularly distributed microstructures.…”
Section: Introductionmentioning
confidence: 99%
“…Its mechanical behaviour is anisotropic as a consequence of its composition, with collagen fibres that run in different directions (Zhurov et al, 2007). Between the collagen fibres there are tissue fluids that provide a damping behaviour, which enables the ligament to offer a viscous and timedependent response (Komatsu, 2010). Some works have shown that the elastic response of the PDL is nonlinear (Pini et al, 2002).…”
Section: Theoretical Biomechanics 144mentioning
confidence: 99%